2004
DOI: 10.1038/sj.bjc.6601899
|View full text |Cite
|
Sign up to set email alerts
|

DARPP-32 expression arises after a phase of dysplasia in oesophageal squamous cell carcinoma

Abstract: This is the first report to correlate DARPP-32 immunoreactivity (dopamine and cAMP-regulated phosphoprotein, M r 32 000) to clinicopathological status in human cancer. DARPP-32 is recognised as a neuronal protein. A recent study demonstrated that DARPP-32, and a truncated isoform t-DARPP, are overexpressed in gastric carcinoma during the process of carcinogenesis. The biological function of DARPP-32, however, is still unclear. The purpose of this study was to clarify the roles of DARPP-32 and t-DARPP in oesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…We have observed a similar trend for Darpp-32 and t-Darpp overexpression in a small number of common adenocarcinomas, including breast, colon, lung, and prostate (8). However, a recent study has shown that esophageal squamous cell carcinomas frequently overexpress Darpp-32 but not t-Darpp (9). In a related study, amplification and overexpression of ERBB2, which coincides at the same locus as DARPP-32 (17q12q21), was found in f10% of both diffuse-type and intestinal-type gastric cancers (31).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We have observed a similar trend for Darpp-32 and t-Darpp overexpression in a small number of common adenocarcinomas, including breast, colon, lung, and prostate (8). However, a recent study has shown that esophageal squamous cell carcinomas frequently overexpress Darpp-32 but not t-Darpp (9). In a related study, amplification and overexpression of ERBB2, which coincides at the same locus as DARPP-32 (17q12q21), was found in f10% of both diffuse-type and intestinal-type gastric cancers (31).…”
Section: Discussionsupporting
confidence: 73%
“…We have recently cloned DARPP-32 (AF464196) and its novel truncated isoform t-DARPP (AY070271) from adenocarcinoma of the stomach with 17q amplicon (6,7). In addition, we and others have recently documented the overexpression of Darpp-32 in a variety of common adenocarcinomas, such as those of the colon, esophagus, breast, and prostate (8,9).…”
Section: Introductionmentioning
confidence: 73%
“…We previously identified PPP1R1B/DARPP-32 as a cancer gene (29). PPP1R1B/DARPP-32 is now known to be overexpressed in several tumors, such as adenocarcinomas of the breast, colon, esophagus, and stomach (33)(34)(35)(36). We recently showed that PPP1R1B/DARPP-32 is a novel cancer gene with a potent antiapoptotic potential that may contribute to the drug resistance and poor outcome phenotype in UGCs (37).…”
Section: Discussionmentioning
confidence: 99%
“…We have identified a truncated isoform of Darpp-32, t-Darpp, as a novel gene that is expressed in cancer (8). t-Darpp is overexpressed in several common adenocarcinomas, such as those of the colon, esophagus, breast, and prostate (9)(10)(11)(12)(13)(14). We have reported that overexpression of t-Darpp provides antiapoptotic potential to cancer cells in a p53-independent mechanism (15).…”
Section: Introductionmentioning
confidence: 99%